Criminal Liability in Banking Crimes in Idonesia - Aprilia Ricardo (Zona Law And Public Administration Indonesia, 2023)
The banking industry today has a close relationship with human economic life. By running a bank business, banking supports the demands of human life. In accordance with Law No. 10, 19988 on Banking, a bank is a company that receives...deposits from the general public and uses the funds to lend money to the general public or use it in other ways to improve people's standard of living. According to Law No. 10,1998 on Banking, a bank is an enterprise that accepts public deposits and uses the funds to lend to the public or use them in other ways to improve the standard of living of the general public. The following are examples of criminal behavior in the banking industry: licensing is known as illicit bank crimes, bank business secrets, offenses relating to the Bank's "commercial operations" and crimes relating to" the Bank's supervision and direction. So what about bank accountability for the four forms of criminal behavior is closely related to behavior that may be carried out by bank management or staff